Great people decisions : - Fernandez Araoz, Claudio (John Wiley & Sons, 2007)
Fernandez-Araoz provides compelling evidence for why making great people decisions is essential for anyone who aspires to become a great leader or build a great company. If you follow the sage advice he offers in this book, you are sure to make great people decisions